Microorganism Distribution that Causes Abortionin Females of Fallujah City (Medico Legal Update, 2020)
The research included the study of microbiological content in the reproductive system and urinary tractinfections for abortions cases in the city of Fallujah. For this purpose, 121 swabs were taken, including50 swabs of the genital system (27 Vaginal and 23 Endo cervical swabs) and 71 swabs of urine. The resultrefer to that only 27 samples gave negative bacterial growth, while the other 94 samples showed growthof more than one species of bacteria on different media. The bacterial population isolated from the urinewas highest (81.7%), followed by vagina (74.1%) and the endo cervical (69.6%%).The results showedthat the ratios of the isolated bacterial samples were Escherichia coli (54.4%), Streptococcus agalactiae(17%), Staphylococcus aureus (12%), Klebsiella (8.5%), Pseudomonas aeruginosa (5.3%), Proteus (1%)and Candida albicans (1%). The E. coliwas the most common type bacterial isolates.Antibiotic sensitivitytests against 24 antibiotics were reveal that bacteria Escherichia colihave multiple resist against differentantibiotics, most isolates were highly resistant to Aztroenam followed by cefotaxime and ciproflaximerespectively, while their resistance to other antibiotics varied.The results also showed that Proteus whichisolated from urine samples and Candida albicans which isolated from vaginal specimens were the lowestpercentage, where only one isolate was obtain for each and the Candida abicans were resistant to all ofdifferent antibiotics used in this study.